SINTESIS DAN KARAKTERISTIK MEMBRAN NILON YANG BERASAL DARI LIMBAH BENANG - Epa Rosidah Apipah (Jurnal Biofisika, 2014)
Recently, the technology of membrane is developed directly. Many attractive things of membrane is able to be studied, therefore many ideas emerged on the aspect of synthetic membrane fabrication from many materials, furthermore it is able to used substituting for the function of natural membrane. The purpose of this study are able to know and study the influence of the TiO2 additional on the compounds of the nylon thread in market and on the characteristic of electricity and mechanics. The membrane was fabricated by a phase inversion method on weight variation. The characterizations were done which were the characteristic of electricity (impedance, capacitance, conductance and loss coefficient), the characteristic of mechanics (compression and attraction) and the analysis of on the compounds of the nylon membrane using FTIR. The most optimum characteristic of mechanics are the membrane with nylon weight of 3.5 g and 6.0 g, furthermore from the mechanics characteric was treated the TiO2 dopping. the compounds of the nylon membrane was observed by using FTIR which showed that exist PO4 in the natural membrane and the TiO2 dopped membrane